Poetic purposes in the potry of Andalosian women until Almohad era. - Hattaab, Slman; Sliman , Nabil; Syrafi, Yaser (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
Poetry was and still is the expression of the human being and its feelings. Moreover, it carried at the same time the feature of the historical document which was dated to many of the things that history itself failed to do. The research showed that the documentary value that appeared in more than one aspect: Such as the historical, literary, urban, social and industrial aspects. He referred to the politics of the era of the kings of the sects, the flourishing of the literary movement, and the great level of urbanism they reached, as well as its summary of social life and customs, and its focus on what the industries reached in documentary form. As it is in its living form, despite the passage of time on it in a manner that carries the attribute of history and dives in the depths of the soul to express what is inside it another time.